Analisis Kritik Mimetik pada Lirik Lagu “Celoteh Camar Tolol Dan Cemar” Karya Iwan Fals - Febrina, Nidia (Lembaga Bale Literasi, 2024)
This study aims to analyze the mimetic phenomena contained in the lyrics of the song by Iwan Fals Celoteh Camar Totol and Cemar and to convey the contents of the song in detail so that readers can understand the meaning conveyed through this study. This research method uses a qualitative descriptive approach. The techniques in this study consist of three techniques, namely data collection techniques, data analysis and presentation of results. Based on the results of the analysis of the lyrics of the song Celoteh Camar Tolol and Cemar by Iwan Fals, the lyrics of this song have a meaning of social criticism of the government regarding the sinking of KMP Tampomas II. This song describes the suffering of the victims of the incident. This song is related to the sinking of the KMP Tampomas II ship in 1981, a major tragedy in the history of Indonesian shipping.